Răspuns:
[tex] {x}^{3} - 2 {x}^{2} = - 45 \\ \\ {x}^{2} (x - 2) = - 45[/tex]
Acum, trebuie sa il scriem pe -45 ca pe produsul unui patrat perfect si un alt numar.
avem posibilitatile:
a) -45 = 25 × (-3)
b) -45 = 1 × (-45)
c) -45 = 9 × (-5)
[tex]a) \: \: x - 2 = - 3 \\ x = - 1 \\ {x}^{2} = 25 \: \: \: \\ nu \: \: se \: \: verifica [/tex]
[tex]b) \: \: x - 2 = - 45 \\ \\ x = - 43 \\ \\ {x}^{2} = 1 \: \: \\ nu \: \: se \: \: verifica[/tex]
[tex]c) \: \: x - 2 = - 5 \\ \\ x = - 3 \\ \\ {x}^{2} = 9[/tex]
Vedem ca solutia de la punctul c) este buna.
Succes! ♡♡♡